Precision medicine for cardiovascular disease: learning lessons from cardiomyopathies - Sedaghat-Hamedani, Farbod; Katus, Hugo; Meder, Benjamin (Herz, 2018)
Evidence-based medicine has considerably advanced the treatment of highly prevalent cardiovascular diseases. Its implementation was driven by multicenter interventional trials in treatment and placebo cohorts, propelling numerous biomedical innovations toward standard of care. While a uniform treatment can be effective in such disease cohorts (“one size fits all”), it neglects the genetic and phenotypic individuality of a single patient and his or her disease. Accordingly, a recent observation was made that several newer “mega” trials, demanding considerable resources for their execution, showed statistically significant differences in outcome, however, with small overall efficacies that render implementation in the clinics unlikely. To overcome this concerning development, new methods for individualized treatment of cardiovascular disease are required. Rarer conditions, such as distinct cardiomyopathies, may deliver the blueprint for a paradigm shift: deep and precise phenotyping of individual patients by a multimodal approach and development of targeted treatments for smaller groups (“one treatment for many”) or even for single patients (“one treatment of some”).